Abstract Reasoning and Arithmetic Ability Lead to Academic Success of the Accountancy Students in a Private Non-Sectarian University - Ferrater-Gimena, Judy Ann O.; Biore, Christopher; Bigcas, Bernadette U. (JPAIR Institutional Research, 2015)
The desirable results that most Filipinos value closely associates with academic success; therefore, it is significant. The foremost goal of a university is to produce globally competitive graduates. The study explored the relationship between psychometric examination and academic performances of the Bachelor of Science in Accountancy (BSA) students in a higher educational institution; and proposed a program level intervention plan to decrease the attrition rate of students. The study enthused on Robert Gagne’s Conditions of Learning Theory, which stipulates different levels of learning. There were 56 research subjects, utilizing descriptive-correlational design. Cramer’s V test was also used to examine the relationship between the two measured variables. The findings exhibited that most of the students had an average intelligence quotient and high academic performance. The results revealed that there were significant relationships between abstract reasoning and the arithmetic ability of the students to their academic performance. Thus, the Accountancy students should be given intensive academic training on disciplines and subject areas that make use predominantly of arithmetic ability and analytical skills so that they can survive the rigorous academic training in the program. The “Big Brother Culture” will be set up, wherein the students in the higher years are given authority to tutor and coach the students in the lower years.
Keywords: Education; intelligence; IQ; abstract reasoning; language comprehension; academic performance; descriptive-correlational design; Cebu City Philippines